Study on ionic conduction of solid bio-polymer hybrid electrolytes based carboxymethyl cellulose (CMC)/polyvinyl alcohol (PVA) doped NH4NO3 - M. A., Saadiah; Ahmad Salihin, Samsudin (AIP Publishing, 2018)
Carboxymethyl cellulose (CMC)/ polyvinyl alcohol (PVA) blend (80/20 wt %) as host solid bio-polymer electrolytes complexed with different weight percentage ratios of NH4NO3 were prepared via solution casting approach. Impedance spectroscopy was carried out to disclose the electrical response of the CMC/PVA hybrid electrolytes as a function of various weight percentage of NH4NO3 salt. It is found that the CMC/PVA blend complexed with 30 wt % of NH4NO3 was demonstrated relatively higher room temperature conductivity by the order of 10−4 S/cm. The dielectric behaviour has been analyzed via complex permittivity (ε*) and complex modulus (M*) which varies anomalously with percentage of NH4NO3 confirms the non-Debye behaviour. Besides that, the temperature dependent dc conductivity of polymer electrolyte seems to obey Arrhenius relation, and the activation energies decrease with an increase in NH4NO3. Thus, confirming their potential as promising candidates of all-solid-state proton conducting electrolyte in the electrochemical devices.